Excess complement activation is associated with adverse outcomes in women with hypertensive disorders of pregnancy (2018)
ABSTRACT: Objective Complement activation occurs in normal pregnancy, but excess activation is associated with preeclampsia. Terminal complement activation generates C5b-9, the lytic membrane attack complex, which mediates organ damage. We hypothesize that activation of C5b-9 is increased in women with hypertensive disorders of pregnancy and adverse outcomes Study Design We assessed urine and plasma C5b-9 levels in hypertensive subjects from project COPA (COmplement and Preeclampsia in the Americas), an IRB approved, multi-center observational study, which enrolled subjects from 6 centers and 3 cities in Colombia (Bogotá, Cartagena and Medellín; Nov 15-Jul 16). Hypertensive subjects enrolled in blocks by gestational age ( ≤ or ≥ 34 weeks) and diagnosis (ACOG criteria): 1. chronic hypertension (CHTN); 2. gestational hypertension (GHTN); 3. preeclampsia (PE) and; 4. PE with severe features (PE-SF). COPA was powered for PE-SF (n=100). Clinical data, urine and plasma were collected by trained coordinators, with C5b-9 measured by enzyme linked immunosorbent assays (Human C5b-9 ELISA, BD Biosciences). Maternal and neonatal outcomes were assessed individually and as composite outcomes. Data were analyzed by Chi-square, t-test and logistic regression Results 293 subjects were evaluated [CHTN (n=42), GHTN (n=92), PE (n=58), PE-SF (n=101)]. Adverse maternal and neonatal outcomes, by plasma C5b-9 quartiles 1-4 (pC5b9, Q1-4), are shown in Table 1. Composite maternal outcomes were increased with low pC5b9 (Q1, ≤1443 ng/ml), particularly for those ≥ 34wks (OR 2.93, 95% CI 1.0-8.6, p=0.05). For neonates, preterm birth (PTB) was increased with lower pC5b9 levels (PTB, 2870 ± 1904 vs. term, 3572 ± 2262 ng/ml, p=0.006). Adverse outcomes, by urine C5b-9 (uC5b9) quartiles, are shown in Table 2. They were more common with high uC5b9 levels (Q4, ≥8.49 ng/ml), predominantly due to increased kidney injury (OR 3.0, 95%CI 1.1-8.4, p=0.036) and PTB (OR 2.0, 95% CI 1.2-3.5, p=0.01) Conclusion We describe a novel pattern of complement activation (low plasma / high urine C5b-9), which associates with adverse maternal and neonatal outcomes in women with hypertensive disorders of pregnancy. We postulate that excess complement activation results in kidney injury and depletion of complement factors in plasma, with resultant pregnancy complications.